Body image of people over 50 in Spain measured using the BSQ test - Sánchez Cabrero, Roberto; Martínez López, Fernando; Euán Ramirez, Reyna Guadalupe (My University, 2020)
Objectives: To show the body image of people over 50 in Spain using the Body Shape Questionnaire test (BSQ), taking into account attribute variables of great interest such as age, gender, sentimental status, habitat (rural or urban) and the season of the year in which the test is done (winter or summer). Data description: The results obtained show the current state of the body image of 176 people in the process of ageing in Spain. The data collected from the participants are organised taking into account attribute variables of signifcant impact on body image such as age, gender, having a stable partner, habitat (rural or urban) and the season of the year in which the test is done (winter or summer). These data are especially useful to show how body image changes over the time, depending on the diferent attributes and according to diverse emotional and social situa¿ tions. They can be used in studies on body image, eating disorders or studies that assess the importance of physical appearance in someone¿s self-esteem regardless of age group, geographic area or personal emotional circumstances. Keywords: Body image, Body satisfaction, Maturity, Old age, Elderly